EFFECTIVENESS OF INSTAGRAM REELS MEDIA IN CHEMISTRY LEARNING ON STUDENT LEARNING MOTIVATION - Bahriah, Evi Sapinatul; Anzani, Annisa Audina (JCER (Journal of Chemistry Education Research), 2025)
In the 21st century, learning is increasingly sophisticated but the utilization of technology by teachers is not optimal so that students are less motivated to learn chemistry and have an impact on learning outcomes. Implementing Instagram reels as a learning resource can make chemistry learning more interesting, creative, and innovative so that it is possible to increase students' chemistry learning motivation. The purpose of this study was to determine how the effectiveness of Instagram reels as a learning resource on students' chemistry learning motivation. The research method used was quasi experiment with nonequivalent control group design. The instrument used was a learning motivation questionnaire. The Mann Whitney test results showed an Asymp. Sig. value of 0.000 <0.05 so that H0 is rejected and H1 is accepted. Thus, it can be concluded that the implementation of Instagram reels as a learning resource effectively increases students' chemistry learning motivation.